Pengaruh literasi digital, media sosial dan pengetahuan kewirausahaan terhadap minat berwirausaha mahasiswa akuntansi Universitas Muhammadiyah Riau - Filia, Sarahana; Rodiah, Siti; Samsiah, Siti (Computer Science and Information Technology, 2024)
Based on the results of the researcher's interview with the Head of the FEB UMRI Incubator, Mrs. Dian Puji Puspita Sari, SE., M. Ak, it shows that students' interest in entrepreneurship is still very low. This is shown by the number of Accounting students from the Faculty of Economics and Business (FEB) at Muhammadiyah University of Riau (UMRI) who only have 50 students. This figure is considered very low when compared to the number of FEB UMRI Accounting students as a whole. As accounting students, students are expected to not only master accounting knowledge but also master entrepreneurship knowledge, where this knowledge will later be able to equip students to enter the world of work. Because as students with economic and business backgrounds, students are expected not only to look for work when they graduate from college, but also to be able to create jobs for others by becoming entrepreneurs. This research aims to determine the influence of digital literacy, social media and entrepreneurial knowledge on students' entrepreneurial interest. This research uses a quantitative approach for students taking entrepreneurship courses at the Muhammadiyah University of Riau Accounting Study Program with a sample of 83 people. This research data analysis technique uses validity testing, reliability testing, classical assumption testing and hypothesis testing using multiple linear regression, t test and coefficient of determination test. The research results show that digital literacy, social media, and entrepreneurial knowledge have a partial influence on the entrepreneurial interest of students in the Accounting Study Program at Muhammadiyah University of Riau.